Enantioselective and diastereoselective Mukaiyama-Michael reactions catalyzed by bis(oxazoline) copper(II) complexes. - Evans, D; Scheidt, K; Johnston, J; Willis, M (2001)
The scope of highly enantioselective and diastereoselective Michael additions of enolsilanes to unsaturated imide derivatives has been developed with use of [Cu((S,S)-t-Bu-box)](SbF6)2 (1a) as a Lewis acid catalyst. The products of these additions are useful synthons that contain termini capable of differentiation under mild conditions. Michael acceptor pi-facial selectivity is consistent with two-point binding of the imide substrate and can be viewed as an extension of substrate enantioselection in the corresponding Diels-Alder reactions. A model analogous to the one employed to describe the hetero Diels-Alder reaction is proposed to account for the observed relation between enolsilane geometry and product absolute diastereocontrol. Insights into modes of catalyst inactivation are given, including spectroscopic evidence for inhibition of the catalyst by a dihydropyran intermediate that evolves during the course of the reaction. A procedure is disclosed in which an alcohol additive is used to hydrolyze the inhibiting dihydropyran and afford the desilylated Michael adduct in significantly shortened reaction time.